Effect of Surface Wettability on Frictional Conditions during Scrubbing Using Polyvinyl Acetal Brush. (27th February 2015) - Hara, Y.; Sanada, T.; Fukunaga, A.; Hiyama, H.
Abstract : To gain insight into the mechanisms of polyvinyl acetal (PVA) roller brush cleaning in semiconductor device fabrication, we measure the shear force between four types of PVA brushes and several surfaces and evaluate the effect of the brush rotation speed and surface wettability on the shear force. We simultaneously measure the normal force to evaluate the coefficient of friction (COF). The shear force between the brush and surface is affected by the surface wettability, and the COF is found to decrease and approach 0.5 as the brush rotation speed increases. At low rotation speeds, the COF of hydrophobic surfaces is large (almost 1.0), whereas that of hydrophilic surfaces is small. These results imply that the brush directly makes contact with the surface and that the real contact area of the PVA brush increases with the contact time. In addition, the contact and absorbed water behavior between a brush nodule and the surface was observed using a high-speed video camera. The amount and direction of water seeping out of the nodule depend on the rotation speed and surface wettability. The results indicate that the water motion during nodule contact plays an important role in determining the friction.